2022
DOI: 10.1186/s12938-022-00996-7
|View full text |Cite
|
Sign up to set email alerts
|

Psychological status and physical performance are independently associated with autonomic function

Abstract: Background Falls among older adults have become a global concern. While previous studies have established associations between autonomic function indicator; heart rate variability (HRV) and blood pressure variability (BPV) with fall recurrence, as well as physical inactivity and psychological disorders as risk factors for falls, the influence of physical activity and psychological status on autonomic dysfunction observed among older fallers has not been adequately investigated. The aim of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Disability typically begins with an increase in IADL dependence [ 9 , 10 ]. In addition, a study reported a direct correlation between depressive symptoms and perceived stress, which may lead to greater IADL dependence [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Disability typically begins with an increase in IADL dependence [ 9 , 10 ]. In addition, a study reported a direct correlation between depressive symptoms and perceived stress, which may lead to greater IADL dependence [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Those with depression may exhibit poor disease control, medication use, and social interaction, and may experience difficulties with personal mobility or the performance of independent self-care tasks [ 13 16 ]. Depression resulting from long-term blood sugar control and treatment [ 9 , 10 ], affects a patient’s dietary and medication behaviors [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%